EMPOWERING NON-OPTION TEACHERS OF STUDENTS WITH HEARING IMPAIRMENT THROUGH CONTINUOUS PROFESSIONAL DEVELOPMENT - Yahya, Siti Farisah; Rashid, Syar Meeze Mohd; Khairuddin, Khairul Farhah; Yusuf, Yuzaila (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Malaysia’s inclusive education policy affirms the right of all learners to quality education in line with Sustainable Development Goal 4 (SDG 4). However, implementation remains challenging when non-option teachers, general teachers without formal training in special education for hearing impairment are placed in special schools, Special Education Integration Programme (SEIP) or inclusive classrooms. These teachers face pedagogical, psychological and systemic barriers such as limited sign language proficiency, low confidence and inadequate institutional support. Drawing on national and international literature, this concept paper synthesizes these challenges and proposes a three-dimensional continuous professional development (CPD) framework grounded in Vygotsky’s Zone of Proximal Development (ZPD) and the Universal Design for Learning (UDL). The framework focuses on three dimensions: knowledge through flexible micro-modules, skills through hands-on training, mentorship, and Virtual Reality/Augmented Reality simulations and reflective practice through professional learning communities (PLCs). By positioning CPD as a transformative mechanism, the paper highlights its potential to strengthen teacher competence, resilience and professionalism. As a result, students with hearing impairments are more likely to experience equitable, inclusive and meaningful learning opportunities.